Trends of Components of the Metabolic Syndrome in German First Graders Throughout 10 Years: The PEP Family Heart Study. (5th July 2012) - Haas, Gerda-Maria; Bertsch, Thomas; Schwandt, Peter
Abstract : Although childhood overweight and obesity are increasing worldwide, some countries report trends for stabilization. However, the trend for the potentially atherogenic components of the metabolic syndrome (MetS) in children and adolescents is not well understood. Therefore, the purpose of this study was to analyze the trend of the five components of over 10 years in 2228 first graders aged 6 years. Waist circumference (WC) remained mainly unchanged between 1994 and 2003 whereas the other four components continuously decreased. In boys and girls mean values of triglycerides (−25.9% and −28.6%, resp.), HDL cholesterol (−19.8% and −23.4%, resp.), fasting glucose (−7.3% and −9%, resp.), systolic (−3.8% and −4.1%, resp.), and diastolic (−10.2% and −9.7%, resp.) blood pressure significantly decreased. Whereas the prevalence of abdominal adiposity was stable at baseline and after 10 years (−1% in boys and +2% in girls), the prevalence of hypertension, hypertriglyceridemia, low HDL-C, and glucose was very low without any trend.